Statius Thebaid VII : a commentary - Smolenaars, Johannes Jacobus Louis. (Mnemosyne, Supplements, 1994)
The epic poem the Thebaid by P. Papinius Statius, written about AD 80 to 92, deals with the fraternal strife between Oedipus' sons Eteocles and Polynices for the mastery of Thebes. Book VII describes the forced march of the Seven and their arrival at Thebes, Jocasta's vain attempt at mediation and Amphiaraus' spectacular katabasis . This book is the first which deals with Thebaid VII since Barth (1664) and Amar andamp; Lemaire (1825-30). Apart from being a commentary in the philological sense, it examines in close detail the poet's mannered style and analyses the text as a system of intertextual references. In addition to Homer and Vergil, specific passages from Euripides, Lucan, Seneca and especially Valerius Flaccus were exploited by Statius to create his challenging imitation. The identification of these sources offers the key to interpret and evaluate the poet's artistic intentions. The Introduction discusses Statius' technique of multiple imitation. The information brought together has been made easily accessible by full indexes and an appendix listing the passages imitated by Statius.